Including younger children in science-related issues using participatory and collaborative strategies: a pilot project on urban biodiversity - Campos, Rita (2022)
Young children are actors usually excluded from political decisions and also from many science communication projects. Participatory science communication models can help to connect their everyday life with both local policies and science-related content. Using visual methodologies for engagement, we aimed at understanding what preschool children prefer in the city landscape. Results show how young children envision a “better city” and how that construction might defy current scientific knowledge. It further illustrates how science communication can be used to co-produce new knowledge, contributing to the debate about people's needs and perceptions related to science-based options.